2010
DOI: 10.1021/ja101281e
|View full text |Cite
|
Sign up to set email alerts
|

Probing Valence Orbital Composition with Iron Kβ X-ray Emission Spectroscopy

Abstract: A systematic study of 12 ferric and ferrous Kbeta X-ray emission spectra (XES) is presented. The factors contributing to the Kbeta main line and the valence to core region of the spectra are experimentally assessed and quantitatively evaluated. While the Kbeta main line spectra are dominated by spin state contributions, the valence to core region is shown to have greater sensitivity to changes in the chemical environment. A density functional theory (DFT) based approach is used to calculate the experimental va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
603
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 262 publications
(656 citation statements)
references
References 67 publications
50
603
2
1
Order By: Relevance
“…In this DFT emission spectroscopy approach transition-bar-positions are deduced directly from orbital -rather than state -energy differences and relative peak intensities for the transitions from any final state to the initial core-hole state are given through the respective transition dipole moment expectation values based on the DFT orbitals mentioned above. [50] All spectra obtained with BP86-D3/def2-TZVP were shifted by a constant value of 20.2 eV to match the experimental positions as it is typically done to account for the lower accuracy of DFT core orbitals compared to valence orbitals which leads to an overestimation of core orbital energies. [51] The orbital plotting was performed using the program Avogadro.…”
Section: Computational Sectionmentioning
confidence: 99%
“…In this DFT emission spectroscopy approach transition-bar-positions are deduced directly from orbital -rather than state -energy differences and relative peak intensities for the transitions from any final state to the initial core-hole state are given through the respective transition dipole moment expectation values based on the DFT orbitals mentioned above. [50] All spectra obtained with BP86-D3/def2-TZVP were shifted by a constant value of 20.2 eV to match the experimental positions as it is typically done to account for the lower accuracy of DFT core orbitals compared to valence orbitals which leads to an overestimation of core orbital energies. [51] The orbital plotting was performed using the program Avogadro.…”
Section: Computational Sectionmentioning
confidence: 99%
“…The V2C XES have been previously reported. [10,21] [Color figure can be viewed in the online issue, which is available at wileyonlinelibrary.com.] and their projections into their calculated V2C XES sspectrum, [21] showing the asymptotic behavior for the energy of the fragments Fe 3d , Fe 4p , C 4À 2s , C 4À 2s using values of n ¼ 1, 2, 3, 5, 10 (from left to right) and considering only the alpha set of orbitals.…”
Section: Mapping Of Molecular Orbitals Into Absorption and Emission Smentioning
confidence: 99%
“…Within these ORCA output files, the user can load and analyze ORCA output files (for both restricted or unrestricted solutions) corresponding to: (1) single-point calculations; (2) single-point calculations with X-ray emission spectroscopy (XES) and X-ray absorption spectroscopy (XAS) based on a single-particle model computations [10] ; (3) single-point calculations with time dependent DFT calculations [11,12] ; and (4) broken symmetry calculations. [13] …”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the usual approach is to take into account spatial variations in the scalar and vector potentials to a given order in this multipole moment expansion. As simple as this strategy appears to be, a truncated expansion may introduce an unphysical and nontrivial dependence of molecular response properties on the choice of gauge origin, 3,8,9 and it was only recently demonstrated that origin-independent results for spectral absorption intensities can be retrieved to arbitrary order in the propagation vector by retaining all contributing terms to the oscillator strength to the same order. 10 In the vast majority of theoretical work, light-matter interactions are described within the electricdipole (ED) approximation.…”
Section: Introductionmentioning
confidence: 99%